Citizen Views on Punishment: the Difference between Talking and Deciding - Bergoglio, María Inés (Oñati Socio-Legal Series, 2016)
In 2004, the Province of Córdoba, Argentina implemented lay participation in criminal decisions by means of Law 9182. The law was passed within a context of national debate concerning efficient measures to fight against insecurity and crime. These debates were brought about by a social movement led by Juan Carlos Blumberg, which demanded harsher penalties and judicial reform as means to improve urban safety.Data obtained in two public opinions studies, conducted in 1993 and 2011, are used to analyze trends in attitudes towards criminal punishment, including issues such as the image of criminals or opinions on capital punishment. The revision also includes the influence of the fear of crime on attitudes towards punishment.The analysis of citizen views on punishment extends beyond public opinion data to the judicial field, reviewing how these views are expressed during jury service. Using a set of 213 sentences decided between 2005 and 2012, juror and judge decisions on the same cases are compared.